F08 Factors influencing research participation in Huntington's disease: clues from Southern and Eastern Europe. (12th September 2022) - Júlio, Filipa; Arnesen, Astri; Blanco, Ruth; Schepper, Beatrice De; Sousa, Dina De; Lis, Danuta; Olsen, Svein Olaf; Papantoniou, Giorgos; Ristolainen-Kotimäki, Saija; Tretyakova, Marina; Umakhanova, Zaynab; ,
Abstract : Background: One major obstacle to preventive clinical trials in Huntington's disease (HD) is that persons at risk for HD (HDRisk) and persons with premanifest HD (PreHD) are often distant from clinical and research sites. Understanding their specific needs regarding trial participation is crucial to bring them closer to research. Aims: This work aimed to determine which factors affect the willingness of persons with HDRisk and with PreHD to participate in research and check for differences across European regions. Methods: The European Huntington Association created two online surveys to assess the factors influencing research participation in Spain and Russia. These countries were compared on questions about research experience and knowledge, sources of research information, reasons for getting involved and not getting involved in research, and factors preventing and facilitating participation. Results: 128 persons from Spain and 59 persons from Russia were heard. All showed high motivation to participate in trials, despite their limited research experience and knowledge. Importantly, fundamental differences were found in the reasons driving Spanish and Russian research participation. The Spanish engagement relies on altruistic reasons and is influenced by the relationship with professionals. The Russian engagement relies on individual benefits and is influenced by negative emotions and poor access to professionals. Conclusions: Distinct HD communities are highly motivated to participate in research, albeit their limitations. The uneven access to care and research across Europe seems to influence the factors underlying this motivation. Our findings highlight the relevance of country-specific interventions to encourage informed research participation in preclinical HD.